Experiences of libraries reclassifying from the Dewey Decimal Classification to the Library of Congress Classification scheme and their implications to Silliman University Library - Yso, Lorna T. (Institute of Library Science, University of the Philippines Diliman, 1984)
This study aimed to find out the experiences of nine Philippine academic libraries in reclassifying their retrospective collection from the Dewey Decimal to the Library of Congress classification scheme and their implications to Silliman University Library. Specifically, this study aimed to find out the year when these libraries started their reclassification projects, the reasons for reclassifying, the preparations that the projects entailed, the procedures adopted, the policies decided upon, the staff involved in reclassification work; the budget for the project, the problems in reclassification, and the benefits that resulted from it.